2008
DOI: 10.3382/ps.2008-00017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Broiler Performance and Carcass Yields When Fed Diets Containing Transgenic Maize Grains from Event DP-Ø9814Ø-6 (Optimum GAT), Near-Isogenic Control Maize Grain, or Commercial Reference Maize Grains

Abstract: A genetically modified maize (Zea mays L.) line that contains the Optimum GAT trait (event DP-Ø9814Ø-6; 98140) was produced by integration of the gat4621 and zm-hra genes. The expressed GAT4621 and ZM-HRA proteins confer tolerance to the herbicidal active ingredient glyphosate and acetolactate synthase-inhibiting herbicides, respectively. The objective of this study was to compare the nutritional performance of 98140 maize grain to nontransgenic maize grain in a 42-d feeding trial in broiler chickens. Diets we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…This finding is consistent with those of previous studies in which no biologically significant differences in organ indices (McNaughton et al, 2008) or serum biochemical parameters (Appenzeller et al, 2009) were observed between animals fed diets prepared with GM or non-GM grain. This suggests that a diet prepared from PTC has no unintended effects on serum biochemical parameters and organ weight as compared to a CC-based diet.…”
Section: Resultssupporting
confidence: 93%
“…This finding is consistent with those of previous studies in which no biologically significant differences in organ indices (McNaughton et al, 2008) or serum biochemical parameters (Appenzeller et al, 2009) were observed between animals fed diets prepared with GM or non-GM grain. This suggests that a diet prepared from PTC has no unintended effects on serum biochemical parameters and organ weight as compared to a CC-based diet.…”
Section: Resultssupporting
confidence: 93%
“…This finding agrees with the results of previous studies that have confirmed laying hen performance is not affected by GM plants as compared to their conventional counterpart [26], [27]. Comparative studies [28], [29] with broilers fed GM maize and its isogenic non-GM varieties also showed that there were no adverse effects on the growth performance parameters. Likewise, no significant difference in growth performance parameters of pigs [30], steers [31], cows [32], fishes [33], or rats [34] receiving a non-GM diet or a GM plant-based diet has also been reported.…”
Section: Discussionsupporting
confidence: 92%
“…Other researchers have similarly reported a lack of diet-related or biologically significant differences in growth performance, organ yields, and carcass or individual parts yields between broilers fed diets formulated with GM maize grains and broilers fed diets formulated with non-GM near-isogenic control maize grains. 6,[60][61][62][63][64][65] The observed lack of effects in this study demonstrates that DP23211 maize grain is as safe and nutritious as maize grain not containing event DP-Ø23211-2.…”
Section: Organ and Carcass Yieldsmentioning
confidence: 67%